2020
DOI: 10.20546/ijcmas.2020.912.386
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Toxicity Assessment of Acephate and it’s Amelioration By Picrorhiza kurroa in Female Wistar Rats

Abstract: Acephate is an organophosphate foliar spray insecticide of moderate persistence with residual systemic activity of about 10-15 days. Acephate and its primary metabolite, methamidophos, are toxic to Heliothis spp. that are considered resistant to other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…of malathion showed oxidative alterations and many histopathological lesions in the liver and kidney tissues (Selmi et al, 2018); severe damage was observed in hepatic tissue including prominent enlargement of sinusoids, infiltration of mononuclear cell, dilation, hemorrhage and necrosis, while it was degeneration of glomeruli, Bowman's capsules and associated tubules structure in kidney. Londhe et al (2020) reported degeneration in liver and kidney of 1/20 th of LD 50 of acephate treated female rats.…”
Section: Resultsmentioning
confidence: 98%
“…of malathion showed oxidative alterations and many histopathological lesions in the liver and kidney tissues (Selmi et al, 2018); severe damage was observed in hepatic tissue including prominent enlargement of sinusoids, infiltration of mononuclear cell, dilation, hemorrhage and necrosis, while it was degeneration of glomeruli, Bowman's capsules and associated tubules structure in kidney. Londhe et al (2020) reported degeneration in liver and kidney of 1/20 th of LD 50 of acephate treated female rats.…”
Section: Resultsmentioning
confidence: 98%